2022
DOI: 10.1002/adfm.202210850
|View full text |Cite
|
Sign up to set email alerts
|

Piezo‐Augmented and Photocatalytic Nanozyme Integrated Microneedles for Antibacterial and Anti‐Inflammatory Combination Therapy

Abstract: Wound infection is arguably the most common, and potentially the most devastating, complication of the wound healing process. The ideal treatment strategy has to eliminate bacteria, alleviate inflammation, and promote wound healing and skin formation. Herein, a multifunctional heterostructure is designed consisting of ultrasmall platinum–ruthenium nanoalloys and porous graphitic carbon nitride C3N5 nanosheets (denoted as PtRu/C3N5), which concurrently possesses piezoelectric enhanced oxidase ‐mimic nanozyme ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…Composed of ultrafine Pt–Ru nanoalloys and porous graphitic carbon nitride C 3 N 5 nanosheets, the materials (PtRu/C 3 N 5 ) with the capability of both piezoelectrically enhanced oxidase‐mimic nanoparticle activity and photocatalytic H 2 production, can simultaneously achieve antibacterial and anti‐inflammatory effects of wound infections in a short time. [ 60 ]…”
Section: Application Of Piezocatalytic Nanomaterials In Medicinementioning
confidence: 99%
“…Composed of ultrafine Pt–Ru nanoalloys and porous graphitic carbon nitride C 3 N 5 nanosheets, the materials (PtRu/C 3 N 5 ) with the capability of both piezoelectrically enhanced oxidase‐mimic nanoparticle activity and photocatalytic H 2 production, can simultaneously achieve antibacterial and anti‐inflammatory effects of wound infections in a short time. [ 60 ]…”
Section: Application Of Piezocatalytic Nanomaterials In Medicinementioning
confidence: 99%
“… [ 121 ] Silk fibroin, silicon Arrays:- Height:- Shape: conical Strength: 0.5 ​N/Needle VEGF Porous structures enhanced the drug loading capability; Liquid diffused along the microfluidic channel for detecting biomarkers in wound secretion; Microelectronic circuits were integrated to sense the motion state of wound areas. [ 123 ] HA Arrays:- Height: 600 ​μm Shape: conical Strength: Platinum–ruthenium nanoalloys and porous graphitic carbon nitride C3N5 nanosheets Improving transdermal drug delivery efficiency [ 124 ] …”
Section: Mns For Istrmentioning
confidence: 99%
“…The modification of microneedles and their substrate materials is a proven strategy to enhance microneedle drug delivery (Su et al, 2020;Deng et al, 2022). Shi et al (2023) loaded platinum ruthenium nanoalloy modified nanosheets onto hyaluronic acid-based microneedles and applied nanozyme antibacterial therapy, which showed good antibacterial and antiinflammatory properties. González García et al (2019) prepared carboxymethyl cellulose based microneedles containing AgNPs, and the results showed that they had significant antibacterial activity against both gram negative and positive bacteria.…”
Section: Other Nanomaterialsmentioning
confidence: 99%